Internalization of Islamic Character Values Through a Reflective Approach and Pedagocial Sprituality of Islamic Religious Education Teacher : A Case Study - Purnama, Andi (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: This study aims to analyze the process of internalizing Islamic character values through a reflective approach and to examine the role of pedagogical spirituality of Islamic Religious Education teachers, as well as to formulate a synergistic model for sustainable character formation in vocational high school students. Methodology: This study employed a qualitative approach with a case study design. Data were collected using participatory observation, in-depth interviews, and documentation techniques. Informants were selected through purposive sampling, including PAI teachers, school principals, and students. Data analysis applied the Miles and Huberman interactive model, involving data reduction, data display, and conclusion drawing. Main Findings: The findings reveal that the reflective approach effectively enhances students’ logical awareness of Islamic character values. Pedagogical spirituality of teachers, expressed through sincerity, role modeling, and spiritual practices (riyadhoh), strengthens students’ inner transformation. The synergy between reflective reasoning and spiritual influence accelerates the internalization process, resulting in more consistent, conscious, and sustainable character behavior among students. Novelty/Originality of this study: This study offers a novel integrative model combining reflective pedagogy and pedagogical spirituality in Islamic character education. It advances existing knowledge by emphasizing the balanced interaction between cognitive reasoning and spiritual influence, providing a holistic framework for character internalization that moves beyond conventional instructional methods toward deeper affective and transformative learning processes.